Global Food Inequality and Systemic Risks to Development, Human Security, and Political Stability - Sanjoyo (Pusbindiklatren Bappenas, 2025)
This commentary reflects on the persistent global food inequality and its cascading impacts on sustainable development as part of ongoing discourses on food security and the SDGs highlighted in recent issues. Rather than restating statistical summaries, this piece provides a systems-level perspective on how structural food injustice—both globally and in Indonesia—requires transformative policy responses. The globe makes enough food every day to feed 8 billion people. More than 700 million people go to bed hungry, which is ironic. Not because there isn't enough food being made, but because the global distribution system is dysfunctional and access is very unfair (FAO, 2023). This global food disparity has become a major concern for international organizations such as FAO and WFP, given its implications for global development and stability” (FAO, 2021; WFP, 2023). On one hand, rich countries are producing excessive amounts of food and discarding millions of tons of it, while on the other hand, poor countries continue to struggle with hunger. Not only is this a moral issue, but it is also important for the social and economic stability of the whole world. The global food crisis is caused by more than just problems with distribution. It is also affected by systemic factors, including climate change, geopolitical conflicts, and unfair trade policies between countries (FAO, 2022). Climate change causes floods and droughts that hurt agriculture in many places in the world. War in places like Ukraine and Sudan is making problems with the global food supply system worse. At the same time, wealthier countries often provide their farmers with big subsidies to preserve their interests (UNCTAD, 2022). This makes it hard for developing countries to compete in the global market. All of this makes the framework of inequality in the world's food system even stronger.